Sternal Gland Scent-Marking Signals Sex, Age, Rank, and Group Identity in Captive Mandrills - Stefano Vaglio; Pamela Minicozzi; Riccardo Romoli; Francesca Boscaro; Giuseppe Pieraccini; Gloriano Moneti; Jacopo Moggi‐Cecchi (2015)
Mandrills are one of the few Old World primates to show scent-marking. We combined ethological and chemical approaches to improve our understanding of this behavior in 3 zoo-managed groups. We observed the olfactory behavior performed by adults and adolescents ( N = 39) for 775h. We investigated the volatile components of sternal scent-marks using gas chromatography-mass spectrometry and compared volatile profiles with traits of the signaler. Males marked more than females and within each sex the frequency of scent-marking was related to age and dominance status, but alpha males scent-marked most frequently and particularly in specific areas at the enclosure boundaries. We identified a total of 77 volatile components of sternal gland secretion, including compounds functioning as male sex pheromones in other mammals, in scent-marks spontaneously released on filter paper by 27 male and 18 female mandrills. We confirmed our previous findings that chemical profiles contain information including sex, male age and rank, and we also found that odor may encode information about group membership in mandrills. Our results support the hypotheses that scent-marking signals the status of the dominant male as well as playing territorial functions but also suggest that it is part of sociosexual communication.